2019
DOI: 10.1155/2019/9514703
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic Acid Enriched Fraction fromPerilla frutescensLeaves Strongly Protects Indomethacin-Induced Gastric Ulcer in Rats

Abstract: Gastric ulcers are a common problem in upper gastrointestinal tract (GI) disorders. Nonsteroidal anti-inflammatory drugs (NSAIDs) are one of the most aggressive factors leading to inducing gastric ulcers. Natural products with lower toxicity and safety are currently sought as a potential source to minimize the effect of the gastric ulcers. Perilla frutescens or Nga-mon (in Thai) leaves are rich in rosmarinic acid (RA), which has antioxidant, anti-inflammatory, and anticancer effects. This study investigates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 44 publications
2
28
0
1
Order By: Relevance
“…Acacetin and diosmetin inhibited H. pylori growth, which causes human gastrointestinal diseases [ 49 ]. Kangwan et al reported that rosmarinic acid acts as a protective agent against gastric ulcers caused by indomethacin [ 50 ]. Based on the results of previous studies, five core components were considered to play a critical role in reducing gastritis induced by inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Acacetin and diosmetin inhibited H. pylori growth, which causes human gastrointestinal diseases [ 49 ]. Kangwan et al reported that rosmarinic acid acts as a protective agent against gastric ulcers caused by indomethacin [ 50 ]. Based on the results of previous studies, five core components were considered to play a critical role in reducing gastritis induced by inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The ethanol-induced ulcer model (used by most authors to study the preventive effect of plant extracts, administered before the induction of the ulcer) [40,47] is mainly characterized by desquamation, severe and marked erosion of the epithelial surface, vacuolation and necrosis, a disorderly and loose arrangement of the epithelial cells, as well as infiltrates of neutrophils/eosinophils [21,29]. The same types of lesions are present in the case of ulcers induced by NSAIDs, but the phenomena are more discreet and regeneration is faster [27,45]. The histological features, emphasized by the present study, showed that the hydroalcoholic extract of Prunella vulgaris L can be successfully utilized as a gastric mucosa protector, but the therapeutic doses and the time of administration, after a diagnosis of peptic ulcer, should be carefully evaluated.…”
Section: Representative Images Of Ulcers and Associated Lesions In Thmentioning
confidence: 99%
“…Some of the methods used for the assessment of the gastrodefensive effects of plant extracts or synthetic drugs are the pylorus ligation model [35, 36] and the peptic ulcer models induced by HCL, HCL/ethanol [37, 38], acetic acid [39], and NSAIDs [40]. The ethanol-induced ulcer model in rats or mice still remains one of the most used method in the investigation of the therapeutic and/or preventive activities of active compounds, especially those from plant extracts.…”
Section: Introductionmentioning
confidence: 99%